Automated Detection of High Exudates and Cotton Wool Spots in Diabetic Retinopathy - Ponnammal, S (International Journal of Computer Sciences and Engineering, 2025)
Diabetic Retinopathy is the damage caused to the retina of the eye due to the diabetes. There are a large number of people, who are suffering from Diabetic Retinopathy that leads to blurring of vision or even blindness, if not treated at an early stage. Hence it is important to detect Diabetic Retinopathy at an earlier stage and provide treatment otherwise it may lead to vision demages. This paper presents to identify or earlier detection of the High Exudates and Cotton Wool Spots in Diabetic Retinopathy through Color transformation and Image Enhancement using FFT.